Alternative Cell Sources for Liver Parenchyma Repopulation: Where Do We Stand? - Tine Tricot; Jolan De Boeck; Catherine Verfaillie (Cells, 2020)
Acute and chronic liver failure is a highly prevalent medical condition with high morbidity and mortality. Currently, the therapy is orthotopic liver transplantation. However, in some instances, chiefly in the setting of metabolic diseases, transplantation of individual cells, specifically functional hepatocytes, can be an acceptable alternative. The gold standard for this therapy is the use of primary human hepatocytes, isolated from livers that are not suitable for whole organ transplantations. Unfortunately, primary human hepatocytes are scarcely available, which has led to the evaluation of alternative sources of functional hepatocytes. In this review, we will compare the ability of most of these candidate alternative cell sources to engraft and repopulate the liver of preclinical animal models with the repopulation ability found with primary human hepatocytes. We will discuss the current shortcomings of the different cell types, and some of the next steps that we believe need to be taken to create alternative hepatocyte progeny capable of regenerating the failing liver.